Biometry and maturation of Sesbania punicea (Cav.) Benth. seeds - Grzeça, Gislaine Tais; Emer, Aquélis Armiliato; Winhelmann, Mara Cintia; Paolazzi, Joana; Lazarotto, Marília; Schafer, Gilmar (Acta Iguazu, 2021)
The objective of the study was to evaluate the biometry of fruits and seeds of S. punicea in order to determine the point of collection for production of seedlings of the species. The fruits of S. punicea were collected from plants in situ in Barra do Ribeiro, RS. In the laboratory, they were separated by staining in: stage 1, 2 and 3. Fruits and seeds were measured with digital caliper (mm), counting the number of seeds and locules. At each stage water content, seed dry matter and germination test were evaluated. For this last one, four replications of 25 seeds were placed in germination chamber during 16 days, photoperiod of 12 hours and temperature of 25ºC. The variables analyzed were germination, germination speed index, average germination time, percentage of normal and abnormal seedlings, and hard seeds. It was observed that in stage 2 the seeds have larger dimensions, a higher percentage of germination and formation of normal seedlings, and a higher rate of germination speed. It is concluded that fruits must be harvested at stage 2 of maturation, as seeds have the highest rates of germination and normal seedlings, as well as the lowest rates of insect damage.